Konsumsi Jilbab Ditinjau Dari Perspektif Ekonomi Islam (Studi Kasus: Mahasiswa Jurusan Ekonomi Islam STEBI Tanggamus) - Inggi Satria; Nurul Farida (Dinar Islamic Review, 2021)
The fashion world which continues to grow rapidly at this time has also led to the development of various models and various types of hijab. In the past, the hijab was only used as a cover for the genitals in Islamic law, but now in addition to covering the genitals, the hijab is also a style of dress to make it look attractive, as a sign of social identity, to seek satisfaction, as well as a channel for hobbies and a place to follow trends. This also happened to the student of the Islamic Economics Department, STEBI Tanggamus. In choosing the goods to be consumed, female students often make purchases of hijabs based on developing trends, if the hijab looks attractive, the motivation of female students to buy hijab will be greater, in the end, this consumption pattern will lead to consumption patterns that are not moderate and also excessive. This view of life is very different from the concept of Islamic values. Because Islam teaches a moderate (reasonable) consumption pattern, neither excessive nor outrageous. The formulation of the problem in this study is what factors influence the consumption of hijab by Islamic Economics Department students at STEBI Tanggamus, and whether its implementation is in accordance with the concept of Islamic Economics. The purpose of this study is to find out what are the factors that influence the consumption of female students' headscarves and to find out whether these factors are in accordance with the concept of Islamic economics. The method used in this study is a qualitative method, with primary data obtained through observation, and questionnaires. The object of the research is a student of the Islamic Economics Department, STEBI Tanggamus. The results showed that with the hijab trend that was booming in the market and almost every time it changed, making female students follow it, the goal was to want to look more fashionable and not want to be out of date or old-fashioned.